2014
DOI: 10.1021/jf503047a
|View full text |Cite
|
Sign up to set email alerts
|

Biological Functionality of Soyasaponins and Soyasapogenols

Abstract: Soyasaponins are a group of structurally complex oleanane triterpenoids primarily found in soybeans and have diverse biological properties. The recent investigations and findings (since 2000) regarding the biological functions of soyasaponins and their aglycones, including their anti-inflammatory, antimutagenic, anticarcinogenic, antimicrobial, and hepato- and cardiovascular-protective activities, are herein summarized. The primary conclusion is that the use of soyasaponins and soyasapogenols in functional foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
66
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(77 citation statements)
references
References 61 publications
2
66
0
3
Order By: Relevance
“…Soyasaponins are amphiphilic oleanane triterpenoid glycosides with polar sugar chains conjugated to a nonpolar pentacyclic ring . In recent years, soyasaponins have attracted great interest by nutritionist and food researchers because of their multiple health‐promoting bioactivities such as antimutagenic, anticarcinogenic, antioxidant, hepatoprotective, anti‐viral, and cholesterol lowering effects . Interestingly, recent studies reveal that soyasaponins, ranging from crude extracts to purified monomers, exhibited anti‐inflammatory properties .…”
Section: Introductionmentioning
confidence: 99%
“…Soyasaponins are amphiphilic oleanane triterpenoid glycosides with polar sugar chains conjugated to a nonpolar pentacyclic ring . In recent years, soyasaponins have attracted great interest by nutritionist and food researchers because of their multiple health‐promoting bioactivities such as antimutagenic, anticarcinogenic, antioxidant, hepatoprotective, anti‐viral, and cholesterol lowering effects . Interestingly, recent studies reveal that soyasaponins, ranging from crude extracts to purified monomers, exhibited anti‐inflammatory properties .…”
Section: Introductionmentioning
confidence: 99%
“…Azad) (1416). Soyasaponins are oleanene-type triterpenoid saponins with polar sugar chains and a non-polar pentacyclic ring structure (17).…”
Section: Introductionmentioning
confidence: 99%
“…Soyasaponins are oleanene-type triterpenoid saponins with polar sugar chains and a non-polar pentacyclic ring structure (17). These metabolites are generally divided into four main groups on the basis of their aglycone (soyasapogenol) structure, referred to as groups A, B, E and DDMP (2,3-dihydro-2,5-dihydroxy-6-methyl-4-pyrone) (14). Group A soyasaponins contain bidesmosides with two sugar chains at the C-3 and C-22 position of soyasapogenol A.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[22] Recent studies reported that soyasaponins presented a wide range of health benefits, including memory impairment prevention, immune adjuvant activities, and cytoprotective and hepatoprotective effects. [232223242526] Although crude soyasaponins-rich extract has been shown effective on acute alcohol-induced hepatotoxicity in mice,[27] the protective mechanism and monomer compound activities are still unknown, which limited their application in functional foods.…”
Section: Introductionmentioning
confidence: 99%